The Country of Coal - Frank, David (Labour / Le Travail, 1988)
The article reviews and comments on "British Coalminers in the Nineteenth Century: A Social History," by John Benson, "Independent Collier: The Coal Miner as Archetypal Proletarian Reconsidered," edited by Royden Harrison, "Keir Hardie: The Making of a Socialist," by Fred Reid, "By the Sweat of their Brow: Womee Workers at Victorian Coal Mines," by Angela John, "Work Relations in the Coal Industry: The Hand-Loading Era, 1880-1930," by Keith Dix, "The Miner's Freedom: A Study of the Working Life in a Changing Industry," by Carter Goodrich, "Life, Work, and Rebellion in the Coal Fields: The Southern West Virginia Miners, ,1880-1922," by David Corbin, and "Power and Powerlessness: Quiescence and Rebellion in an Appalachian Valley," by John Gaventa.
Keywords: BENSON; John; BRITISH Coalminers in the 19th Century: A Social History (Book); BY the Sweat of Their Brow: Women Workers at Victorian Coal Mines (Book); HARRISON; Royden; INDEPENDENT Collier: The Coal Miner As Archetypal Proletarian Reconsidered (Book); JOHN; Angela; Nonfiction; REVIEWS; books

Strikes in Nova Scotia, 1970-1985 - Frank, David (Relations Industrielles / Industrial Relations, 1988)
This article reviews the book, "Strikes in Nova Scotia, 1970-1985," by C.H.J. Gilson.

On the Job: Confronting the Labour Process in Canada - Heron, Craig; Storey, Robert H.; Steedman, Mercedes; Frank, David; Foster, John Bellamy; Lowe, Graham S.; Reiter, Ester; Radforth, Ian; Strong-Boag, Veronica; Kealey, Gregory S.; Craven, Paul; Traves, Tom; et al. (McGill-Queen's University Press, 1988)
Every day millions of Canadians go out to work. They labour in factories, offices, restaurants, and retail stores, on ships, and deep in mines. And every day millions of other Canadians, mostly women, begin work in their homes, performing the many tasks that ensure the well-being of their families and ultimately, the reproduction of the paid labour force. Yet, for all its undoubted importance, there has been remarkably little systematic research into the past and present dynamics of the world of work in Canada. The essays in this volume enhance our understanding of Canadians on the job. Focusing on specific industries and kinds of work, from logging and longshoring to restaurant work and the needle trades, the contributors consider such issues as job skill, mass production, and the transformation of resource industries. They raise questions about how particular jobs are structured and changed over time, the role of workers' resistance and trade unions in shaping the lives of workers, and the impact of technology. Together these essays clarify a fundamental characteristic shared by all labour processes: they are shaped and conditioned by the social, economic, and political struggles of labour and capital both inside and outside the workplace. They argue that technological change, as well as all the transformations in the workplace, must become a social process that we all control. –Publisher's description
Available at Internet Archive to readers with print disabilities: https://archive.org/details/isbn_0773505997